Changes in hematological parameters, plasma cortisol, and acetylcholinesterase of juvenile rockfish, Sebastes schlegelii supplemented with the dietary ascorbic acid - Jun-Hwan Kim; Ju-Chan Kang (Aquaculture Reports, 2016)
Juvenile rockfish (mean length 13.6 ± 1.4 cm, and mean weight 53.6 ± 4.2 g) were fed diets containing different levels of ascorbic acid (0, 50, 100, 200, and 400 mg/kg) for 4 weeks. Fish were fed twice daily (08:30 and 18:30). The major hematological findings were significant increases in the red blood cell count, hematocrit value, and hemoglobin level in the rockfish fed diets over 100 mg/kg ascorbic acid. The dietary ascorbic acid supplementation caused significant increases in the glucose and total protein, whereas notable decreases were observed in GOT and GPT. However, alterations in calcium and magnesium were not observed by the ascorbic acid supplementation. Plasma cortisol was substantially decreased over 50 mg/kg ascorbic acid. Acetylcholinesterase activity of the rockfish was significantly increased over 200 mg/kg ascorbic acid. In conclusion, the present study indicates that the dietary ascorbic acid supplementation in the rockfish induces considerable increases in hematological parameters, alterations in plasma components, and increase in AChE activity.